Prevalence of food insecurity and satisfaction with on-campus food choices among Australian university students. Issue 4 (8th March 2021) - Murray, Sandra; Peterson, Corey; Primo, Carmen; Elliott, Catherine; Otlowski, Margaret; Auckland, Stuart; Kent, Katherine
Abstract : Purpose: Food insecurity and poor access to healthy food is known to compromise tertiary studies in university students, and food choices are linked to student perceptions of the campus food environment. The purpose of this study is to describe the prevalence, demographic and education characteristics associated with food insecurity in a sample of Australian university students and their satisfaction with on-campus food choices. Design/methodology/approach: An online, cross-sectional survey conducted as part of the bi-annual sustainability themed survey was conducted at the University of Tasmania in March 2020. A single-item measure was used to assess food insecurity in addition to six demographic and education characteristics and four questions about the availability of food, affordable food, sustainable food and local food on campus. Findings: Survey data ( n = 1, 858) were analysed using bivariate analyses and multivariate binary logistic regression. A total of 38% of respondents (70% female; 80% domestic student; 42% aged 18–24 years) were food insecure. Overall, 41% of students were satisfied with the food available on campus. Nearly, half (47%) of food insecure students were dissatisfied or very dissatisfied with the availability of affordable food on campus. A minority of students were satisfied with the availability of sustainable food (37%) and local food (33%) on campus. Originality/value: These findings demonstrate a high prevalence of food insecurity and deficits in the university food environment, which can inform the development of strategies to improve the food available on campus, including affordable, sustainable and local options.